Sustainability Branding and Green Marketing Toward Green Purchase Intention - Derah Sudjaniah; Junef Ismaliyanto; Lu’luatuwwafiroh Lu’luatuwwafiroh; Indira Sascha; Rio Octogi Siregar (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study examines the influence of environmental concern, brand sustainability practice, and green marketing on green purchase intention in Indonesia, while assessing the moderating role of price among digital consumers. Methodology/approach: A quantitative design using Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze data from 350 digital consumers. The measurement model fulfilled validity and reliability criteria (outer loadings > 0.70; AVE > 0.70). The structural model achieved an R² value of 0.394, indicating a moderate explanatory power. Results/findings: Environmental concern (? = 0.192; p < 0.001), brand sustainability practice (? = 0.221; p < 0.001), and green marketing (? = 0.159; p = 0.001) positively influence green purchase intention. Price also shows a positive direct effect (? = 0.139; p = 0.008). All moderating interactions are significant, with the strongest effect found in Price × Green Marketing (? = 0.384; p < 0.001; f² = 0.253), suggesting that perceived price compatibility strengthens the effectiveness of green marketing messages. Conclusion: Green purchase intention in Indonesia is driven by environmental concern, sustainable brand practices, and green marketing. Price does not hinder but instead reinforces these effects, indicating a consumer shift toward valuing sustainability despite premium pricing. Limitations: The study uses self-reported, cross-sectional data from purposive sampling of digital consumers, limiting generalizability across demographic groups and longitudinal behavioral changes. Contribution: This research provides an integrated model that highlights the combined effects of environmental concern, sustainability branding, and green marketing with price moderation, offering empirical insights relevant to green marketing strategies in emerging markets.